Proposal for creation of positron-emission tomography center on the basis of school of medicine and school of physics and technology of Kharkiv National University - Voronko, V.O.; Dronov, R.N.; Shramenko, B.I.; Beloziorov, І.V.; Girka, I.O. (Вопросы атомной науки и техники, 2020)
The creation of a PET center in the Kharkov region is proposed. This is facilitated by the transfer of the cyclotron by the Julich Research Center (Germany) to Kharkiv, which will ensure the development of the diagnostic radiopharmaceutical “Glucose,¹⁸F”. An additional expansion of the treatment base is possible by acquiring a microtron electron accelerator, which will make it possible to produce and use for treatment of cancer the “Ethanol,¹¹C” radio-pharmaceutical and the “Glucose,¹¹C” diagnostic radiopharmaceutical developed at the NSC KIPT.